Occupational diseases and injuries in production emergency medical care (Eurasian Research Bulletin, 2024)
In the article, production technologies are developed in our daily life. Based on this, the health of people working in production enterprises, factories, mines is the main priority, and the methods of health protection for people working in places related to production and technological processes have been described. At the same time, first aid methods were studied